Six ways to get a grip on leveraging the expertise of Instructional Design and Technology professionals - Chen, Weichao; Kleinheksel, A.J. (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
We underutilize the knowledge and skills of Instructional Design and Technology (IDT) professionals, despite the frequent challenges in implementing learning technologies in medical education. This is largely due to a lack of understanding among stakeholders regarding the expertise of IDT professionals and their role in technology implementation processes. We seek to improve technology implementation outcomes by explaining the IDT field’s foundational tenets of a systems perspective and disciplined approach, clarifying the role that IDT professionals can play in educational technology initiatives, and providing guidance on how to foster productive collaborations in pursuit of effective technology-enhanced learning.